The effect of per os vs subcutaneous 123iodine administration on percentage thyroidal radioactive iodine uptake in normal cats - Kevin Cosford; Elisabeth Snead; Matt Hutcheson; Sally Sukut (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Historical and recent literature disagree on whether a higher PO 131I dosage, compared to IV or SC routes, is required for successful resolution of spontaneous hyperthyroidism in cats, necessitating investigation into the effect of PO and injectable radioactive iodine administration on % thyroidal radioactive iodine uptake (RAIU). Hypothesis/Objectives To investigate the effect of PO and SC routes of 123I administration on paired % thyroidal RAIU in euthyroid cats. Specifically, a 1.5‐fold difference (50% relative change) was hypothesized, which in absolute terms can be expressed as a 3.25% increase in the mean %RAIU of 7.04% after PO 123I administration to 10.56% after SC dosing. Animals Seven healthy euthyroid teaching‐research colony cats. Methods A randomized, radiologist‐blinded crossover study comparing %RAIU after PO and SC 123I administration. Results Percentage thyroidal RAIU values (mean ± SD; 95% confidence interval) after PO (4.81% ± 1.63%; 3.30%‐6.23%) and SC (5.26% ± 2.43%; 3.01%‐7.51%) 123I administration were associated with a median within‐pair absolute difference of 0.2% (range: min, 0.1%‐max, 4.9%). Statistical significance was not achieved (P  =  .45). Six of 7 cats had a within‐pair absolute difference of 0.1% to 0.9% (relative change of 4%‐20%), but a single outlier cat had a within‐pair absolute difference of 4.9% (relative change of 108%). Conclusions and Clinical Importance This study did not detect an effect of 123I administration route on paired % thyroidal RAIU in euthyroid cats. However, a type 2 statistical error due to small sample size is possible.